A Pragmatic Analysis of Barack Obama’s “A More Perfect Union” in the Context of Relevance Theory - Muhammad Haroon Jakhrani; Naomi Justin; Muhammad Hassan Shaikh (University of Chitral Journal of Linguistics and Literature, 2024)
This research aims to provide a comprehensive analysis of the ’A More Perfect Union’ speech by Barack Obama using a pragmatic approach. The paper is qualitative and descriptive and uses textual analysis for interpretation. This study utilizes the principles of relevance theory developed by Dan Sperber and Deirdre Wilson to unlock the intricate ways through which Obama powerfully crafted his message to connect, persuade, and resonate with his audience. Through a careful and purposeful examination of the context, implication, and cognitive effects, the paper intends to make known the cognitive mechanisms that Obama employs to establish relevance and get his message across effectively. The presented research work contributes to a deeper knowledge of the pragmatic aspects of political rhetoric and offers insights into the impact of linguistic strategies on the formation of public opinion and debates nowadays.